Consideraciones teóricas respecto de la supervisión de prácticas finales en la Formación Inicial Docente (Educational Perspectives Magazine (REPED), 2023)
At present the following project is being developed by the Program of Education and Teaching of Special Education - Learning Problems In the Special education Department of the Universidad Metropolitana de Ciencias de la Educación: The supervisión of the student-teaching practicum as an instrument to improve the initial teacher formation. The main objective of this project is to understand the different types of practices which the different supervisors implement during such period.Due to its relevance, this project will let us know and reflect upon the diverse supervisión styles which are being implemented in our School and, at the same time, it will permit us to make proposals to better the supervising practices in those teachers who act as supervisors in the final practicum.The following article is part of the theoretical Framework discussion of this project. Its aim is to show some central theoretical aspects which would allow discussing and reflecting upon our actual supervising practices so as to re-orient them to become an instrument to improve initial teacher formation.
Keywords: Practices, Teacher Initial Formation, Supervisión.